Risk factors associated with early childhood asthma: findings from the infant cohort of the longitudinal study of Australian children - Poulos, L; Waters, A-M; Marks, G; Reddel, H; Xuan, W; Ampon, R (My University, 2009)
Background: Development of childhood asthma has been associated with a number of external and inherent factors. Aim: The purpose of this study was to estimate the prevalence of, and risk factors for, early childhood asthma using data from the infant cohort of the Longitudinal Study of Australian Children. Methods: The infant cohort (aged 0–1 years at baseline) was recruited from 2004 (response rate 57%) and re-assessed two years later (response rate 90%). A face-to-face interview was conducted with the primary carer. Asthma was defined as a positive response at age 2–3 years to the question “Has a doctor ever told you that your child has asthma?”. Baseline risk factors including sex, bronchiolitis, passive smoke exposure, breastfeeding, neo-natal intensive care exposure, gestational age, birth weight, and socioeconomic status were investigated using multivariate analysis in a logistic regression model accounting for the survey design. Results: Estimated prevalence of asthma among 2–3 year olds was 14.6% (628/4,580). Reported asthma at this age was significantly, independently associated with the following characteristics measured in the first year of life: bronchiolitis (OR=4.61 (95% CI: 3.41–6.24)), passive smoke exposure (OR=1.83 (95% CI: 1.28–2.62)), and male gender (OR=1.48 (95% CI: 1.15–1.90)). Conclusions: The findings indicate a high rate of diagnosis of asthma in this cohort within the first 3 years of life. The external and inherent risk factors associated with the diagnosis of asthma in this cohort are consistent with those observed in earlier studies. Support: ACAM is a collaborating unit of the AIHW and is funded by the Australian Government Department of Health and Ageing.
Keywords: Children; Health -- Medical conditions; Health and wellbeing; Health; Children; Medical conditions; Health and wellbeing